Effect of Approved Destination Status on Mainland Chinese Travel Abroad1. Issue 3 (September 2014) - Arita, Shawn; La Croix, Sumner; Edmonds, Christopher
<x xml:space="preserve">Abstract</x> Approved Destination Status (ADS) agreements facilitate international leisure travel by Chinese citizens, allowing authorized travel agencies to offer group tour arrangements, including visa applications. The number of destinations with ADS agreements increased from 2 in 1983 to 114 in 2012. Using panel data for Chinese visitor arrivals in 58 countries from 1985 to 2005, we estimate a semi‐parametric matched difference‐in‐differences model of the impact of ADS on overseas departures from mainland China. Treatment with ADS increased Chinese visitor arrivals in the 3‐year period following ADS designation by more than 10 percent annually, with results varying substantially across countries.